Bullous Pemphigoid Triggered by Artificial Hip Made of Titanium Alloy: A Case Report and Review of Triggers for Bullous Pemphigoid - Wen-Zhong Xiang; Jia Deng; Ai-E Xu; Qi Wang; Xiao-Hang Du; Ping Wang (Journal of Dermatologic Research And Therapy, 2015)
Bullous pemphigoid (BP) is one of the most common autoimmune blistering diseases. Here, we report an old woman presented with a 2-month history of bullous lesions located just over the skin of the right thigh and buttock where the orthopedics operation was performed using artificial hip made of titanium alloy and a twenty days history of similar lesions involving the rest of the body gradually.
Keywords: Erythema